Nursing management in the fever clinic in a general hospital under the normalization of prevention and control of COVID-19 (新型冠状病毒肺炎疫情常态化防控期间综合医院发热门诊护理管理实践) - YAN Junjie (闫俊杰); QI Wenjing (綦文婧); LI Jia (李佳); WANG Meiyu (王美玉) (中西医结合护理)
This paper summarized the nursing management in the fever clinic in a general hospital under the normalization of prevention and control of COVID-19. Efforts were made in the following areas such as reorganization of fever clinics, improvement and implementation of the nosocomial infection control system, preparation of relevant medical staff, enhancement of training and assessment, reinforcement learning of relevant regulations and documents, implementation of prevention and control measures, and nursing team building. Moreover, continuous improvement of closed-loop management and outpatient pre-screening triage were effective to prevent and control of nosocomial infection, and ensure the nursing quality in the fever clinic. (本文总结新型冠状病毒肺炎疫情常态化防控期间综合医院发热门诊就诊流程及护理管理实践经验, 通过重组发热门诊, 完善并落实院内感染制度, 筹备相关医护人员, 加强培训和考核, 学习相关规定、文件, 组建护理梯队等, 改进发热门诊闭环管理措施, 优化会诊、转诊流程, 有效避免院内感染, 确保门诊工作的正常开展。)